Household Waste Management for the Achievement Efforts of SDGs in Bulak Surabaya - Sindy Rukmana Pratiwi; F Rooslan Edy Santosa (LPPM NAROTAMA UNIVERSITY, Indonesia, 2018)
The purpose of this study was to determine the conductor description of household waste management in the district of Bulak Surabaya by using studies EHRA (Environmental Health Risk Assessment) where a study of participation in the District/City to understand the conditions of sanitation facilities and hygiene as well as societal attitudes on a household scale. This research was conducted by observation and interview. And the Village of respondents as an area of ??studyassigned randomly. Based upon the results of studies EHRA research in District of Bulak Surabaya , there are 200 respondents, only a small proportion of respondents who perform household waste management around 19.5%, while those who do not perform household waste management, 80.5% ofachievement SDGs taken from point 6